The evaluation of Smart Dentin Replacement (SDR), a year observation study - Buczko, Piotr; Wawrzyn-Sobczak, Katarzyna; Matuszczak, Ewa; Hermanowicz, Adam (Journal of Education, Health and Sport, 2018)
Introduction The size of composite material layer used for restoring hard tissues of a tooth is connected with polymerisation stress which varies between 2.5% and 3.5% of the volume in most composite materials. The value rises with the increase in the portion of the composite material. Thus, there is a necessity of using the technique of layers which can be time consuming in case of extended cavities of hard tissues. The composite material SureFil Smart Dentin Replacement (SDR) Flow turned to be an alternative and seems to be a great turning point in the conservative dentistry. The aim of the study was the evaluation of flowable composite material SDR as the base layer during one year observation. Methods Post-operative sensitivity was evaluated during initial studies after the treatment. During further periodic examinations class II fillings were evaluated as for contact points between neighboring teeth and the presence or absence of gingivitis. All the fillings were evaluated as for secondary caries occurrence. After the treatment, parameters of the experimental material work were compared to traditional composite materials. Results Initial clinical examinations revealed post-operative sensitivity in approximately ¼ of patients next day and 3 days after the filling was completed. The number decreased significantly 7 days after the treatment and decreased to 5% of the patients. The clinical evaluation of contact points showed normal – 100% restoration of contact points in various time intervals. We did not observe any inflammatory condition due to filling overhang or allergic reaction of the gingiva in contact with SDR. The symptoms of secondary caries, confirmed with clinical and radiological examinations, were detected in 7 (4+3) fillings in the period of 12 months of the observation. Clinical condition after 6 months showed 5% of restoration failure while after 12 months it was 7%. Conclusions The results of own studies show high effectiveness and safety of SDR use as the 4mm base layer for fillings of cavities class I and II at least one year after conservative treatment ( layer application) or during one-year-observation.